The pattern of color change in small mammal museum specimens: Is it independent of storage histories given museum-specific conditions? - Sandoval Salinas, Maria Leonor (2018)
Objective: Determination of color and evaluating its variation form the basis for a broad range of research questions. For studies on taxonomy, systematics, etc., resorting to mammal specimens in museum collections has a number of advantages over using field specimens. However, if museum specimens are to be for studying color, they should accurately represent the color of live animals, or we should understand how they differ. Basically, this study addresses this question: How does coat color vary when dealing with specimens of Akodon budini (Budin's grass mouse, Thomas 1918), stored in one museum collection for different periods of time? Results: We measured color values through a spectroradiometer and a diffuse illumination cabin and used the reflectance values in the form of CIELab tri-stimulus values, considering CIE standard illuminant A. We observed that there is a relationship between specimen storage antiquity and pelage color and it seems that it is general for at least a number of small mammals and this could indicate a universal phenomenon across several mammal species and across several storage conditions. Our results, as others, emphasize the importance of considering storage time, among other circumstances, in research studies using mammal skins and where color is of importance.